Medical Educators Satisfaction with Online Learning during the COVID-19 Pandemic: - Mohammed, Luma K.; Alogaili, Methaq H. (Journal of the Faculty of Medicine Baghdad, 2023)
Background: Medical educators’ dissatisfaction may cause them to leave the practice of teaching where it is often hard to replace those who have left. In addition, medical teaching staff dissatisfaction may be an indicator of adverse quality for institution/ university organizations.Objectives: To assess teaching staff satisfaction with online learning during the COVID pandemic at Al-Nahrain University /College of Medicine, Baghdad/Iraq.Methodology: A cross-sectional study included a convenient sample of 50% of the teaching staff participating in the online academic year 2020-2021. The faculty satisfaction questionnaire was taken from the "Bolliger and Halupa" study, based on the validated questionnaire of the Online Course Satisfaction Survey (OCSS) that contains four major categories: Interaction, instructor planning, institutional support, and affordance.Results: The study included 85 medical college teachers from all departments. The total satisfaction level of participants in this study was 25.6% which is considered low. The total satisfaction score given by the participants was (0.98), the highest score (1) was given to the items of affordance questions, and the lowest was given for student-instructor interaction and course design and development (0.79, and 0.89) respectively.Conclusion: The satisfaction of teaching staff with online learning during the COVID-19 pandemic was generally low, especially regarding student-instructor interaction and course design and development